Enzymatic Resolution of 3-oxodicyclopentadiene on a Decagram Scale - Kärki, Katja; Siitonen, Juha H.; Kortet, Sami; Cederström, Mona; Pihko, Petri M. (Synlett, 2018)
The chiral building block 3-oxodicyclopentadiene (1) can be readily resolved on a decagram scale by a short sequence consisting of (1) reduction to the corresponding endo-alcohol, (2) enzymatic oxidative resolution with a ketoreductase enzyme to give (+)-1 and the (+)-form of the endo-alcohol, and (3) reoxidation of the (+)-endo-alcohol with another ketoreductase to give (–)-1. With a selectivity factor of 310, the enantiomeric ratios of the resolved (+)-endo-alcohol and (+)-ketone are both >99:1. Both enzymatic oxidations could be performed with a at least 300:1 substrate/catalyst ratio (w/w).
Keywords: enzymes; oxidation; resolution; alcohols; gram-scale synthesis; tetrahydromethanoindenone